American Epic: The Companion Book to the PBS Series - Bernard MacMahon , Allison McGourty (Touchstone, 2017)
In the 1920s, as radio took over the popular music business, record companies were forced to leave their studios in major cities in search of new styles and markets. Ranging the mountains, prairies, rural villages, and urban ghettos of America, talent scouts discovered a wealth of unexpected talent, and when these performers got their opportunity, their recordings changed music as we know it. Illustrated with dozens of vintage and contemporary photographs, this companion to the 2017 PBS series takes an in-depth look at this renaissance, using essays and interviews to chart the influence of such figures as the Carter Family, Mississippi John Hurt, Charley Patton, and Lydia Mendoza.